Conocimientos, actitudes y prácticas de la salud bucal en adolescentes del Colegio Adolfo Valarezo de la ciudad de Loja - Ramón Herrera, Katherine Michelle (2019)
Oral health is essential in individual well-being, it seems to be a problem for teenagers to carry it out correctly so individual beliefs and attitudes towards proper oral hygiene behaviors are very important to maintain good oral health. In this line of thought, it is suggested to act massively in oral education as the main focus on the curative approach, it is important to emphasize that the more positive the attitudes towards self-care practices applied by adolescents, the greater the likelihood that they will achieve adequate oral health conditions. Objective: “Assess the knowledge attitudes and practices of oral health through traditional techniques in adolescents of 1st and 2nd Baccalaureate of the high school “Adolfo Valarezo” of the city of Loja. Materials and methods: Evaluation study of longitudinal section, with a sample of 50 students aged 15 to 17 years, to whom the questionnaire of knowledge, attitudes and practices of oral health was applied through traditional technique. Results: It was possible to establish that there was no significant statistical difference before and after the intervention in the oral education process, since in the knowledge, attitudes and practices tests, the calculated value was> 0.05 (0.529; 0.805 and 0.894 respectively). In other words, the adolescents in the present study did not improve their knowledge, attitudes and practices in oral health significantly. Conclusions: There was no significant statistical difference in the oral education of the adolescents participating in the study, before and after applying the traditional technique, considering that the oral health intervention was short-term and the corresponding reinforcement was not applied. Keywords: questionnaire, technique application, high school student, oral treatment, promotion